2018
DOI: 10.22159/ajpcr.2018.v11i1.23410
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Nutraceuticals in Prevention and Treatment of Cancer: A Review

Abstract: The objective of the study was to discuss the preventive and treatment of cancer from flavonoids nutraceuticals from our daily dietary source. There has been increasing interest in the research of flavonoids from dietary sources, due to growing evidence of the versatile health benefits of flavonoids through epidemiological studies. Numerous biological activities have been reported. Some clinical trials or meta-analyses have suggested positive associations between flavonoid intake and human health, Several find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As an example, its properties as an antioxidant are well known, and it can also be a therapeutic agent to overcome diseases like inflammation, autoimmune, neurodegenerative disease, and even several types of cancers. It has a low intrinsic toxicity on normal versus cancerous cells, compared with other structurally related flavonoids [52,53]. Notwithstanding its importance, there is a lack of research related to beneficial health potential of apigenin for humans with respect, for example, to inflammation or cognitive performance, another relevant potential application of this substance.…”
Section: Apigenin Biological Potential: From Molecular Aspects To mentioning
confidence: 99%
“…As an example, its properties as an antioxidant are well known, and it can also be a therapeutic agent to overcome diseases like inflammation, autoimmune, neurodegenerative disease, and even several types of cancers. It has a low intrinsic toxicity on normal versus cancerous cells, compared with other structurally related flavonoids [52,53]. Notwithstanding its importance, there is a lack of research related to beneficial health potential of apigenin for humans with respect, for example, to inflammation or cognitive performance, another relevant potential application of this substance.…”
Section: Apigenin Biological Potential: From Molecular Aspects To mentioning
confidence: 99%
“…In addition to above, a scanty information is available on the toxicity of apigenin. It has a low intrinsic toxicity on normal versus cancerous cells, compared with other structurally related flavonoids (Ali et al, 2017;Lotha & Sivasubramanian, 2018). According to Singh et al (2012), the liver damage is induced by oxidative stress, attributed to the regulation of multiple genes by apigenin at higher doses in Swiss mice whereas Seydi et al (2016) found that apigenin, when introduced in different concentration as 10, 20, and 40 µM, raised the mitochondrial parameters like mitochondrial membrane potential, reactive oxygen species level, mitochondrial swelling, and cytochrome C expulsion only in cancerous hepatocytes.…”
Section: B Ioavail Ab Ilit Y and Me Tabolis M Of Api G Eninmentioning
confidence: 99%
“…They are able to induce the apoptosis of cancer cells. These special foods can be used for chemoprevention or as a supportive therapy at treatment of tumor by standard anticancer chemotherapeutics [175,176,177,178,179,180].…”
Section: Other Functional Applications Of Human Supplementsmentioning
confidence: 99%